Insights from individuals with chronic conditions in the context of COVID-19 - B. Stephen Burton; Jonathan Patterson; Mackenzie Robinson; Dhiren Patel; Matt Allison; Kelly Brassil (The Beryl Institute, 2020)
The objective of this prospective survey series was to evaluate knowledge and concerns related to the COVID-19 pandemic among individuals with one or more chronic conditions, including cardiometabolic, autoimmune, respiratory and cancer diagnoses. Two surveys were distributed consisting of up to 55 items (March; n=1069) and up to 71 items (April, n=1126), with 24 items repeated from the first survey. Questions focused on healthcare access, barriers and concerns related to the COVID-19 virus. Descriptive analysis evaluated central tendencies, spread, and frequencies of the demographic data, disease states, and survey results within and between the two survey timepoints. Results from 416 individuals (38.9%) on survey 1 and 425 (37.7%) on survey 2 were analyzed. Participants were predominantly female (85%) and white (67%) with 7% residing in rural areas and 69% employed. Respondents reported an average of 2 chronic conditions and 62% would be classified as "at risk" for COVID-19 complications by the CDC. Only 20% reported a conversation about COVID-19 with a healthcare provider, 9% reported anxiety, 35% indicated loneliness. Level of concern about COVID-19 contracting the disease, cost of treatment/complications, medical access, and process of being treated was associated with increased anxiety (p<0.001) and wearing a facemask (p=0.01). Analysis suggests that analyzing concern and its association with health behaviors and anxiety should be a priority for innovative solutions. Insights into how the COVID-19 pandemic is impacting individuals with chronic conditions are imperative to inform tailored interventions to support individuals at higher risk of serious complications and death. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.